A native and an invasive dune grass share similar, patchily distributed, root-associated fungal communities. (October 2016) - Johansen, Renee B.; Johnston, Peter; Mieczkowski, Piotr; Perry, George L.W.; Robeson, Michael S.; Burns, Bruce R.; Vilgalys, Rytas
Abstract: Fungi are ubiquitous occupiers of plant roots, yet the impact of host identity on fungal community composition is not well understood. Invasive plants may benefit from reduced pathogen impact when competing with native plants, but suffer if mutualists are unavailable. Root samples of the invasive dune grass Ammophila arenaria and the native dune grass Leymus mollis were collected from a Californian foredune. We utilised the Illumina MiSeq platform to sequence the ITS and LSU gene regions, with the SSU region used to target arbuscular mycorrhizal fungi (AMF). The two plant species largely share a fungal community, which is dominated by widespread generalists. Fungi detected on only one species were rare, accounting for a small proportion of the data. The SSU region recovered AMF from more samples and from more Glomeromycota lineages than ITS or LSU. A high degree of turnover among samples was observed, but there was no evidence for strong distance-decay.